Synthesis of Nitriles from Aldehydes and Hydroxylamine Hydrochloride using Anhydrous Sodium Sulphate and Sodium Bicarbonate in Dry Media - B. Shejul, Pravin; H. Kadam, Nitin; V. Vyavahare, Amol; B. Kasawar, Gajanan; Panpaliya, Prashant (Asian Journal of Chemistry, 2010)
A rapid and facile one pot synthesis of nitriles has been carried out in high yields from the corresponding aldehydes and hydroxylamine hydrochloride in the presence of environmentally benign anhydrous sodium sulphate and sodium bicarbonate catalysts in dry media under microwave irradiation.